Creating Reading Habits Through Translation in Turkey (1840–1940) - Erkul Yaǧci, Ahu (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2017)
Although translated books and readers are visibly and inextricably linked, readers, readers’ expectations, attitudes and habits have only been partially analysed in translation research. In a similar vein, the relationship between translation and reader was rather left undiscovered by scholars studying translation/book/reading history. The aim of this paper is to present the findings of my comprehensive doctoral research on the pioneering role translation played in the history of reading and readers in Turkey between 1840 and 1940 by problematizing the relationship between translation, readers and their reading habits. This hundred year period is characterized by an apparent transformation in the literary production (especially in the number of translated works) and the publishing industry, which created an expansion in the number of readers and the development of new forms to suit the needs and tastes of this new readership. Data from a variety of sources including readers’ letters and auto/biographical accounts will be used in this article to investigate readers, their reading habits and the transformative process they experienced through this reading (r)evolution. In the absence of library records and marginalia due to the inherent characteristics of the period under study, these letters and auto/biographical accounts are of primary importance in providing evidence of what and how the readers were actually reading. Their active involvement in the process (of selection and consumption of translated and/or indigeneous works) is also reflected through the views, experiences and perceptions that are present in these letters and accounts.